The reference effect on a retailer's selling strategy with limited initial inventory level and strategic consumer behavior. (July 2022) - Zhao, Nenggui; Wang, Qiang; Wu, Jie
Highlights: Reference price and limited inventory level affect consumers' strategic behaviors. Value of consumers' awareness of stockout risk is examined. Four possible selling strategies are determined for the retailer. Strategy transitions are analyzed to derive optimal conditions for each strategy. Consumers have two different attitudes towards stockout risk. Abstract: Reference price is generally formed in consumers' minds and used to judge the current selling price. In this paper, we consider a retailer owns a limited initial inventory level (IIL) selling to strategic consumers over a selling horizon with a regular period and a potential markdown period. A unique feature but also a significant challenge of this paper is that either reference price or IIL affects the consumers' strategic behaviors and the retailer's selling strategy, especially when the consumers are aware of stockout risk. To explore the single and joint impacts of both two factors and the value of consumers' awareness of the risk, we first present a pricing model in which the consumers are unaware of the risk, we subsequently extend to another model where the consumers are aware of the risk, and we finally conduct numerical experiments to further examine the impacts and the value. The results show that if the consumers are unaware of the risk, a stronger reference effect (RE) will generate more revenue for the retailer, especially when IIL is insufficient. If the consumers realize the risk, the above results heavily depend on their attitude to risk. At this time, a higher IIL will induce more consumers to wait until the markdown period. Besides, the consumers are optimistic towards the risk will enhance the strength of RE and help the retailer to improve revenue, while the opposite is true when the consumers are pessimistic towards the risk. In addition, a sufficient inventory level does not necessarily bring more benefits than the limited inventory level if the consumers are aware of the risk.